2010
DOI: 10.1016/j.cbpc.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenesis and other physiological responses induced by 17-β-estradiol in males of freshwater fish Rhamdia quelen

Abstract: This study investigated the effects of different doses of 17-beta-estradiol (E(2)) in Rhamdia quelen. Groups of males exposed to different doses of E(2) (0.1 mg kg(-)(1), 1 mg kg(-)(1) and 10 mg kg(-)(1)) were compared with non-exposed male and female fish groups. Among the considered biomarkers, no significant differences were observed for micronuclei test, reduced glutathione concentration and lipid peroxidation. All E(2)-treated individuals had decreased glutathione S-transferase activity. Increased catalas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 54 publications
2
24
0
3
Order By: Relevance
“…Werner et al (2003) also reported that MT concentrations were significantly reduced in the livers of lake trout exposed to the high and medium concentrations of ethynylestradiol. Moreover, Costa et al (2010) showed that the levels of MT decreased in the liver of mature male fish (Rhamdia quelen) exposed to the highest E2 dose with a higher E2 level in plasma. Previous studies showed that E2 or other estrogenic compounds might inhibit MT expression by reducing free intracellular Zn being available to bind to the metal responsive elements in the promoters of MTs during Vtg synthesis (Olsson et al, 1995;Gerpe et al, 2000;Werner et al, 2008).…”
Section: Modulation Of Mt Gene Expressionmentioning
confidence: 99%
“…Werner et al (2003) also reported that MT concentrations were significantly reduced in the livers of lake trout exposed to the high and medium concentrations of ethynylestradiol. Moreover, Costa et al (2010) showed that the levels of MT decreased in the liver of mature male fish (Rhamdia quelen) exposed to the highest E2 dose with a higher E2 level in plasma. Previous studies showed that E2 or other estrogenic compounds might inhibit MT expression by reducing free intracellular Zn being available to bind to the metal responsive elements in the promoters of MTs during Vtg synthesis (Olsson et al, 1995;Gerpe et al, 2000;Werner et al, 2008).…”
Section: Modulation Of Mt Gene Expressionmentioning
confidence: 99%
“…Domestic effluents and livestock waste excrete a considerable amount of hormones in addition to agriculture runoffs and industrial sources. The excreted urine contains a large part of the hormones in the form of sulfate and glucuronide conjugates, but the bacterium Escherichia coli in wastewater is able to deconjugate these metabolites due to its β-glucuronidase and sulfatase activity (Aris et al 2014, Costa et al 2010. E2, EE2 and their water soluble sulfate and glucuronide metabolites enter natural streams, rivers, lakes mainly through cleaned wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…That suggests that molecular changes appear in the whole body of treated fishes. Changes are described in the liver, kidneys, and in the brain of two species; in silver catfish (Bagrus filamentosus) and in zebrafish (Danio rerio) (Costa et al 2010, Martyniuk et al 2007). The immune system and the mortality of leucocytes of fishes can also be affected (Bado-Nilles et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of estrogens on the immune systems of Nereidids worms are still unclear. Some studies suggest that E2 can affect immune function in fish, resulting in changes that include leukocyte production and activity (Yamaguchi et al 2001;Moura Costa et al 2010). As a major intracellular antioxidant, GSH plays a crucial role in the maintenance and regulation of the thiol-redox status of the cell, which prevents the oxidation of protein thiol groups, either directly by reacting with reactive species or indirectly through glutathione transferases.…”
Section: Resultsmentioning
confidence: 99%
“…The reported effects of E2 on aquatic species have mainly focused on the endocrine disrupting effects and the mechanisms of action (Osada et al 2003;Maria et al 2008;Ciocan et al 2010). However, some studies have demonstrated that E2 can disrupt non-reproductive endocrine events, namely the stress responses in fish (Teles et al 2005;Maria et al 2008;Moura Costa et al 2010). The immune system of molluscs also represents a significant target for the action of environmental estrogens, as E2 in the nM range (1-100 nM) induces lysosomal destabilisation in Mytilus (Canesi et al 2007).…”
Section: Introductionmentioning
confidence: 99%